Antigen-driven differentiation of naive Ig-transgenic B cells in vitro. - Dustin, L; Bullock, E; Hamada, Y; Azuma, T; Loh, D (1995)
We have established a culture system in which naive B cells bearing a transgenic, chicken OVA (cOVA)-specific Ig differentiate to plasma cells in vitro after interaction with cOVA plus cOVA-specific helper T cells. B cell-enriched populations from Ig-transgenic mice, but not from nontransgenic mice, proliferated after presenting nanomolar concentrations of cross-linked cOVA to DO11.10 (cOVA plus IAd-specific) T cells. After 6 to 9 days of culture with Ag and specific T cells, the B cells acquired a plasma cell phenotype and secreted the transgene-derived Ig at high levels. Engagement of B cell surface Ig was not essential for primary B cell differentiation. Differentiating B cells enlarged, clustered, and acquired two plasma cell markers, Syndecan and CD43. B cell CD45 isoform expression changed: the B220 isoform was lost in a T cell-dependent manner, whereas the CD45RB isoform was gained in a T-independent manner. Although unstimulated B cells survived less than 72 h in vitro, those in Ag-stimulated cultures showed reduced early death, a surge of proliferation at 3 to 5 days, and increased death late in the culture. Using a large population of naive B cells of defined antigenic specificity permits us to study a primary immune response to an Ag, rather than to less physiologic polyclonal stimuli. Because all steps of differentiation occurred in vitro, they are easily accessible for study. This coculture system provides an opportunity to observe Ag-specific T cell-B cell collaboration.